PERLINDUNGAN HUKUM TERHADAP PESERTA BPJS KESEHATAN MENURUT UU NOMOR 24 TAHUN 2011 TENTANG BPJS DI DESA BANDAR SETIA KECAMATAN PERCUT SEI TUAN - Qori Rizqiah H Kalingga, S.H.I., MA; Dewi Aprilianti; Apriyanti Sembiring; Casmitro Sinaga (Universitas Quality, 2021)
The implementation of the BPJS Health program in its implementation has not gone wellenough, because there are still BPJS Health participants who experience complaintswhen getting health services at the Community Health Service Center (Puskesmas),especially in Bandar Setia Village, Percut Sei Tuan District. In fact, social security is aconstitutional mandate as stated in the 1945 Constitution in Article 28-H and Article 34paragraph 2 of the Amendment. The government developed social security and was only able to follow up on it in 2004, namely through Law Number 40 of 2004 concerning theNational Social Security System (SJSN), to implement the mandate of SJSN, Law Number24 of 2011 concerning the Social Security Administering Body was born. The formationof this BPJS as an effort to realize the welfare of the community. In the article in theBPJS Law it is stated that PT Askes (Persero) is tasked with preparing BPJS Healthoperations in implementing the health insurance program, as well as preparing thetransfer of assets and liabilities, employees, rights and obligations from PT Askes(Persero) to BPJS Health. In this case, the Puskesmas is also a health service providerwho is responsible for implementing legal protection related to the rights of patients orBPJS Health participants in obtaining health services. There are still obstacles faced bythe Puskesmas, especially in Bandar Setia Village in providing health services to BPJSHealth participants, which is a risk from the implementation of Law Number 24 of 2011concerning BPJS. However, there are several efforts made by the Puskesmas in BandarSetia Village to fulfill the rights of BPJS Health participants, including providinginformation and education to BPJS Health participants as needed.